2004
DOI: 10.1080/13552600412331289041
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of motivation for behaviour change among sex offenders against children: An investigation of the utility of the Stages of Change Questionnaire

Abstract: A better understanding of motivation for behaviour change among sex offenders against children would improve treatment programmes designed to modify sexual offending behaviour. However, investigation of this issue is limited by lack of theoretically and empirically sound measures of motivation for behaviour change among sex offenders. This paper reports on two studies that were conducted to investigate the psychometric properties (validity, reliability, and social desirability) of the Stages of Change Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
11
1
Order By: Relevance
“…The questionnaires include the University of Rhode Island Change Assessment Scale (URICA: McConnaughy, DiClemente, Prochaska, & Velicer, 1989;McConnaughy, Prochaska, & Velicer, 1983), the Readiness to Change Questionnaire (RCQ: Heather & Rollnick, 1993), and the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES: Miller & Tonigan, 1996). Of these scales, the URICA is the most widely used and psychometrically investigated across settings and populations (Carey et al, 1999;Eckhardt et al, 2004;Levesque et al, 2000;Tierney & McCabe, 2004). The URICA is a 32-item scale, designed to yield summary scores corresponding to the Precontemplation, Contemplation, Action, and Maintenance stages (McConnaughy et al, 1983(McConnaughy et al, , 1989.…”
Section: Stage Of Change Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaires include the University of Rhode Island Change Assessment Scale (URICA: McConnaughy, DiClemente, Prochaska, & Velicer, 1989;McConnaughy, Prochaska, & Velicer, 1983), the Readiness to Change Questionnaire (RCQ: Heather & Rollnick, 1993), and the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES: Miller & Tonigan, 1996). Of these scales, the URICA is the most widely used and psychometrically investigated across settings and populations (Carey et al, 1999;Eckhardt et al, 2004;Levesque et al, 2000;Tierney & McCabe, 2004). The URICA is a 32-item scale, designed to yield summary scores corresponding to the Precontemplation, Contemplation, Action, and Maintenance stages (McConnaughy et al, 1983(McConnaughy et al, , 1989.…”
Section: Stage Of Change Questionnairesmentioning
confidence: 99%
“…No satisfactory four-factor fit could be established (Eckhardt & Utschig, 2007). Tierney and McCabe (2004) applied a modified version of the URICA to a small sample of child sex offenders. They found no evidence of social desirability biases, and reported acceptable internal and testÁretest reliability and 'construct validity' (p. 242): limited to comparison of the pattern of inter-correlations between the subscales.…”
Section: Urica-based Research With Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex offenders have been found to be at varying stages of readiness to change their behavior (Tierney & McCabe, 2004). Research with other clinical problems would suggest that sex offenders who are at the higher Stages of Change are more likely to change than those at the earlier stages.…”
Section: Resultsmentioning
confidence: 98%
“…This may lead to self-report measures of the SoC being susceptible to social desirability bias, thus, compromising the validity of these measures with this population (McMurran, 2009). Nonetheless, some studies have found psychometric evidence that these stage-based measurements were not influenced by social desirability bias (Polaschek, Anstiss, & Wilson, 2010;Tierney & Mccabe, 2004). Some have argued that the controlled prison setting limits offenders' opportunities to engage in attitudes and behaviours from the maintenance stage (Casey et al, 2005).…”
mentioning
confidence: 95%